2022
DOI: 10.1155/2022/4627972
|View full text |Cite|
|
Sign up to set email alerts
|

IoT Networks and Digital Twin Technology-Based English Classroom Immersive Teaching

Abstract: In order to improve the effect of English classroom teaching, this paper builds an immersive teaching model of English classroom based on IoT networks and digital twin technology. Moreover, in order to reduce the cost of the system, simplify the system structure, and enable learners to observe the stereoscopic display image with the naked eye, this paper builds an immersive hemispherical projection teaching system, designs the overall structure of the system and various components of the hardware, and studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Security and Communication Networks has retracted the article titled "IoT Networks and Digital Twin Technology-Based English Classroom Immersive Teaching" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
“…Security and Communication Networks has retracted the article titled "IoT Networks and Digital Twin Technology-Based English Classroom Immersive Teaching" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%